A very short, fairly interesting and reasonably cheap book about studying strategy - Carter, Chris (Los Angeles SAGE, 2008)
A Very Short, Fairly Interesting and Reasonably Cheap Book about Studying Strategy is a welcoming, lively, and thought provoking account of strategy. It helps students get to grips with strategy's key issues and broad debates and introduce them to the latest ideas that won't yet have been covered in the classroom. Organized into three sections, concepts are made really accessible as the authors first recap the history of strategy as an academic discipline, then evaluate major schools of strategic thought, and conclude by critiquing the latest developments in strategic research.
Includes bibliographical references (p. [143]-154) and index.
Keywords: Strategic planning